Pengaruh Siyasah Syar'iyyah pada Tingkat Kepatuhan Hukum Pidana - Azwarfajri (Bahasa Indonesia, 2026)
The relationship between Islamic public policy (siyasah syar'iyyah) and the level of compliance with criminal law is a crucial issue in the study of Islamic criminal law (jinayah). Siyasah syar'iyyah, as a doctrine that authorizes rulers to formulate policies within the framework of shariah, has significant potential to influence how communities respond to and comply with criminal provisions. This article aims to analyze the influence of siyasah syar'iyyah on the level of public compliance with criminal law. Using a normative-juridical research method with a conceptual and statutory approach, this study finds that siyasah syar'iyyah influences criminal law compliance through several mechanisms: the formulation of ta'zir policies that are responsive to social dynamics, the integration of maqasid al-shariah values that strengthen the moral legitimacy of criminal norms, and the discretionary authority of judges in determining proportionate punishments. The study concludes that the effective implementation of siyasah syar'iyyah principles can enhance public compliance by creating a sense of justice and relevance, although it requires institutional safeguards to prevent arbitrary exercise of power.